The Kantian Background to Cassirer’s Political Commitment and Its Parallelisms with Kant’s Republicanism and Support of the French Revolution - Rodríguez Aramayo, Roberto (Con-Textos Kantianos. International Journal of Philosophy, 2019)
Cassirer’s thought took a radical turn in his mature life, comparable to the one that Kant went through in his last days, and in both cases this was motivated by the political events that they witnessed: the French Revolution in Kant’s case, and the National Socialist ideology in Cassirer’s case. In this work I canvass Cassirer’s way of articulating his own political thought by constantly reclaiming the philosophy of Kant, whose work he never stops referring to, and by constantly reclaiming the values defended by the Enlightenment’s project as a whole, in order to defend, among other things, the idea of a republican constitution and thereby the Weimar Republic. Cassirer decided to fight against Nazism in the field of History of Ideas, choosing Leibniz, Rousseau, Kant and Goethe as his allies. The second part of this work emphasizes this parallelism by unfolding the premises of Kant’s republicanism.